Pemanfaatan Pelepah Pisang Kering Menjadi Tempat Penyimpanan Bumbu Dapur - Banul, Steviana; Kurnia, Maria Eltari; Jeliman, Yuliana Sartika; Yani, Yuliana; Kurniawati, Roswita Angelina; Lambut, Petronela Trinayanti; Jenia, Arsenia (Jurnal Pengabdian Masyarakat Ilmu Keguruan dan Pendidikan (JPM-IKP), 2025)
This study aims to describe the empowerment process of the Wae Palo community, Langke Rembong District, Manggarai Regency, in utilizing dried banana stems as a raw material for making environmentally friendly and economically valuable spice storage containers. Using a descriptive qualitative approach, data was obtained through participatory observation, in-depth interviews, and documentation during the activity. The results indicate that the community is actively involved in all stages of production, from collecting old banana stems, drying, boiling to soften the fibers, knitting, dyeing using natural materials, to the final weaving to form spice storage containers. The resulting products have proven to have adequate mechanical strength, good aesthetics, and maintain the preservation of spices thanks to the banana stems' natural pores that facilitate air circulation. This activity has also had a positive impact on improving skills, environmental awareness, and economic opportunities for the local community. This study confirms that utilizing dried banana stems is not only a solution for reducing organic waste but also has the potential to become a sustainable creative business for rural communities.